Updated European Association of Urology Guidelines on Renal Cell Carcinoma: Nivolumab plus Cabozantinib Joins Immune Checkpoint Inhibition Combination Therapies for Treatment-naïve Metastatic Clear-Cell Renal Cell Carcinoma - Bedke, Jens; Albiges, Laurence; Capitanio, Umberto; Giles, Rachel H; Hora, Milan; Lam, Thomas B; Ljungberg, Börje; Marconi, Lorenzo; Klatte, Tobias; Volpe, Alessandro; Abu-Ghanem, Yasmin; Dabestani, Saeed; et al. (European urology, 2021)
Longer follow-up and new trial data from phase 3 randomised controlled trials investigating immune checkpoint blockade (PD-1 or its ligand PD-L1) in advanced clear-cell renal cell carcinoma (RCC) have recently become available. The CheckMate 9ER trial demonstrated an improved progression-free survival (PFS) and overall survival (OS) benefit for the combination of cabozantinib plus nivolumab. A Keynote-426 update demonstrated an ongoing OS benefit for pembrolizumab plus axitinib in the intention-to-treat population, with a PFS benefit seen across all International Metastatic Database Consortium (IMDC) subgroups, while an update of CheckMate 214 confirmed the long-term benefit of ipilimumab plus nivolumab in IMDC intermediate and poor risk patients. The RCC Guidelines Panel continues to recommend these tyrosine kinase inhibitors + immunotherapy (IO) combination across IMDC risk groups in advanced first-line RCC and dual immunotherapy of ipilimumab and nivolumab in IMDC intermediate and poor risk. PATIENT SUMMARY: New data from trials of immune checkpoint inhibitors for advanced kidney cancer confirm a survival benefit with the combination of cabozantinib plus nivolumab and pembrolizumab plus axitinib and ipilimumab plus nivolumab. These combination therapies are recommended as first-line treatment for advanced kidney cancer.
Keywords: pyridiny; Immune Checkpoint Inhibitors; ipilimumab; lidé; nivolumab; karcinom z renálních buněk; sunitinib; urologie; anilidy; Antineoplastic Combined Chemotherapy Protocols; axitinib; Kidney Neoplasms; protokoly protinádorové kombinované chemoterapie; Carcinoma, Renal Cell; inhibitory kontrolních bodů; Urology; Pyridines; Sunitinib; Nivolumab; Axitinib; nádory ledvin; Ipilimumab; Anilides; Humans